Análisis de la estrategia ambiental del Gobierno Autónomo Descentralizado Municipal del cantón Daule, provincia del Guayas - Camba Vera, Víctor Manuelle (2023)
Environmental strategies are essential for sustainable local development, as they contribute to mitigate climate change, conserve natural resources, promote initiatives in the different actors of the locality focused on the green economy, promote community participation, improve the environmental culture and the quality of life of the population. The objective of this research was to analyze the environmental strategy of the Autonomous Decentralized Municipal Government of Daule. A mixed research approach was used, involving the use of quantitative and qualitative methods. Survey, observation and interview techniques were applied. The sample selected was probabilistic and the type of sampling used was simple random. In particular, the population was composed of inhabitants between the ages of 20 and 69 years. The sample included 381 people who participated in the survey structured in six dimensions that included 13 closed questions. An interview was also conducted with the General Director of Environmental Management of the Decentralized Autonomous Government (GAD) of Daule. Among the most important results of the research are: low environmental culture, lack of training in relation to environmental care, insufficient use of renewable energy, among others. Likewise, the research derived actions that guide the continuous improvement of the relationship with the environment in Daule.